2014
DOI: 10.1071/fp13239
|View full text |Cite
|
Sign up to set email alerts
|

Circadian oscillation and development-dependent expression of glycine-rich RNA binding proteins in tomato fruits

Abstract: Glycine-rich RNA-binding proteins (GRPs) are involved in the modulation of the post-transcriptional processing of transcripts and participate as an output signal of the circadian clock. However, neither GRPs nor the circadian rhythmic have been studied in detail in fleshy fruits as yet. In the present work, the GRP1 gene family was analysed in Micro-Tom tomato (Solanum lycopersicum L.) fruit. Three highly homologous LeGRP1 genes (LeGRP1a–c) were identified. For each gene, three products were found, correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…High HS-down-regulation (28-fold) was observed for an RNA-binding glycine-rich protein (GRP1, solyc10g051390; Table 2 ). Tomato GRP1 was recently shown to be expressed in tomato fruit and was suggested to be linked to circadian processes and to function as an RNA chaperone ( Müller et al, 2014 ). The Arabidopsis homologue, AtGRP8, was shown to be oxidative stress-responsive, participate in cold stress adaptation, serve as an output gene of the circadian clock and suggested as an RNA chaperone ( Ciuzan et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…High HS-down-regulation (28-fold) was observed for an RNA-binding glycine-rich protein (GRP1, solyc10g051390; Table 2 ). Tomato GRP1 was recently shown to be expressed in tomato fruit and was suggested to be linked to circadian processes and to function as an RNA chaperone ( Müller et al, 2014 ). The Arabidopsis homologue, AtGRP8, was shown to be oxidative stress-responsive, participate in cold stress adaptation, serve as an output gene of the circadian clock and suggested as an RNA chaperone ( Ciuzan et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, many studies have shown that GR-RBP genes are highly upregulated in response to cold stress, and examples include AtRZ-1a, GR-RBP4, AtRZ-1b , and AtRZ-1c from Arabidopsis ( Kim et al, 2005 , 2010a ; Kwak et al, 2005 ), BnGRP1 from B. napus ( Kim et al, 2012 ), three GRP2s ( Kwak et al, 2013 ), and GRP7 from C. sativa ( Kwak et al, 2016 ). There are also exceptions, and the accumulation of transcripts and proteins of all the LeGRP1a-c genes from harvested tomato fruit did not increase at 4°C ( Müller et al, 2014 ). In the current study, based on the responses to cold stress conditions, the six cucumber CsGR-RBP s genes could be divided into two categories, with CsGR-RBP2 being enhanced, and the other five not upregulatedby cold stress ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plants and storage conditions: S. lycopersicum WT and PG::preLeGRP1a transgenic lines were grown from seeds as described in Müller et al (2014). Flowers were tagged after pollination and fruits were allowed to develop until different stages according to the number of days after anthesis (DAA) and harvested for analysis or used for the postharvest treatments.…”
Section: Plasmid Construct and Plant Transformationmentioning
confidence: 99%
“…In our previous work, a GR-RBP family, which was called LeGRP1, was characterized in tomato fruits (Müller et al 2014). Three highly homologous LeGRP1 genes (LeGRP1a-c) were identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation